(untitled) (Research, Society and Development, 2025)
Population aging has sparked increasing attention to the need for strategies that promote the physical and emotional well-being of older adults. Among non-pharmacological approaches, Qigong stands out, an Eastern body practice that combines conscious breathing, gentle movements, and concentration. This cross-sectional study aims to understand the relationship between the level of physical activity and emotional indicators and depression among older adults from the UAPI Project in Divinópolis, contributing to a broader understanding of the effects of physical practices on the mental health of this population. An integrative review of a quantitative and qualitative nature was conducted with 127 older adults who answered sociodemographic questionnaires, physical activity assessment instruments, and the Geriatric Depression Scale (GDS-15). Means and standard deviations were calculated for continuous variables and proportions for categorical variables. Student’s t-test (for dichotomous variables) and Analysis of Variance (One-way ANOVA) or the Kruskal-Wallis test (for variables with multiple categories) were used to verify differences in the means or medians of the scores between groups. The results showed no statistically significant association between Qigong practice, physical activity level, and GDS-15 score (p > 0.05). The sample presented an average of 8.27 points on the scale, concentrating on mild to moderate levels of symptoms. Sociodemographic variables were not associated with the outcome. Factors related to social interaction and engagement in educational and collective activities may have contributed to the homogeneity of the scores. The study reinforces the importance of social programs for the mental health of the elderly and recommends longitudinal research on the effects of Qigong.